Computing in the Statistics Curricula: A 10-Year Retrospective. (1st January 2021) - Hardin, Johanna; Horton, Nicholas J.; Nolan, Deborah; Lang, Duncan Temple
Abstract: The Journal of Statistics and Data Science Education special issue on "Computing in the Statistics and Data Science Curriculum" features a set of papers that provide a mosaic of curricular innovations and approaches that embrace computing. As we reviewed the papers we felt that this collection would benefit from the perspective of the authors of the landmark "Computing in the Statistics Curricula" (TAS 2010) paper. We asked Deb and Duncan to take this opportunity to reflect on the landscape when they wrote the paper, to comment on the current situation, and to speculate on the future. Johanna Hardin and Nicholas J. Horton